The Relationship between Advertising and Consumption in India: An Analysis of Causality - Philip, Abey (Faculty of Economics and Business,Universiti Malaysia Sarawak,94300 Kota Samarahan,Sarawak, Malaysia, 2011)
As one of the largest growing economies in the world, India comprises an economic prospect of an immense scale, both as a global base and a domestic market. This article tries to find out whether advertising affect the consumption pattern of India. Advertising is of changing apprehension to companies, as channels burgeon and product offerings become more advanced and bigger and bigger part of the marketing mix. Measurement of advertising and promotional activities is the biggest challenge of companies with in limited time and money. In the marketing literature, the relationship between advertising and sales at the individual firm and industry level has been a hotly debated issue for decades. Existing literature shows that the advertising-sales relationship at the macro level has not gained much attention. This article extends cointegration methodology to validate the evidence of soundness of advertising and consumption pattern of India during the period of 1980-2009. Augmented Dickey-Fuller test, Philips- Peron Test cointegration technique and error correction models were employed to examine association between advertising and consumption. The analysis reveals that there is strong bi-directional relationship between advertising and consumption pattern in India. The increase in advertising expenditure can have a positive impact of consumption irrespective of its lag.